Assessment of ECG during hybrid comprehensive telerehabilitation in heart failure patients—Subanalysis of the Telerehabilitation in Heart Failure Patients (TELEREH‐HF) randomized clinical trial. Issue 6 (9th September 2021) - Orzechowski, Piotr; Piotrowicz, Ryszard; Zaręba, Wojciech; Główczyńska, Renata; Szalewska, Dominika; Pluta, Sławomir; Irzmański, Robert; Kalarus, Zbigniew; Banach, Maciej; Opolski, Grzegorz; Pencina, Michael J.; Kowalik, Ilona; et al.
Abstract: Background: Exercise training in heart failure (HF) patients should be monitored to ensure patients' safety. Electrocardiographic (ECG) telemonitoring was used to assess the safety of hybrid comprehensive telerehabilitation (HCTR). Objective: Analysis of ECG recorded during HCTR in HF patients. Methods: The TELEREH‐HF multicenter, randomized, controlled trial enrolled 850 HF patients with New York Heart Association class I‐III and left ventricular ejection fraction of ≤40%. This subanalysis focuses on 386 patients (aged 62 ± 11 years, LVEF 31 ± 7%) randomized to HCTR. HCTR was telemonitored with a device allowing to record 16‐s fragments of ECG and to transmit the data via mobile phone network to the monitoring center. ResultsIn 386 patients, 16, 622 HCTR sessions were recorded and 66, 488 ECGs fragments were evaluated. Sinus rhythm was present in 320 (83%) and permanent atrial fibrillation (AF) in 66 (17%) patients, respectively. The most common arrhythmias were ventricular and atrial premature beats, recorded in 76.4% and 27.7% of the patients, respectively. Non‐sustained ventricular tachycardia (21 episodes in 8 patients) and paroxysmal AF episodes (6 in 4 patients) were rare. None of the analyzed demographic and clinical characteristics was predictive for onset of the new arrhythmias on exercise. Conclusion: Telerehabilitation in HF patients was safe without the evidence for symptomatic arrhythmias requiring discontinuation of telerehabilitation. Only one mildly symptomatic paroxysmal AF episode led to the short‐term suspension of the training program. The most common arrhythmias were atrial and ventricular premature beats. These arrhythmias did not result in any changes in rehabilitation and therapy regimens.